Malignancy in Clinically Non-toxic Multinodular Goiter - Ali, Mohd Shahjahan; Sarkar, Md Habibullah; Hossain, Syeda Momena (Ibrahim Cardiac Medical Journal, 2021)
Objective: Goiter is a common form of thyroid swelling among population living in areas of iodine deficiency. Of the goiters, non-toxic multinodular goiter (MNG) is the most common and benign form of thyroid disease. However, studies have shown that long-standing MNGs may harbour malignancy. The present study was, therefore, undertaken to ascertain the prevalence of malignancy in clinically diagnosed non-toxic MNGs. Methods: This cross-sectional study was conducted in the Department of Surgery (all four-units) and ENT Department, Rajshahi Medical College Hospital, Rajshahi from July 2007 to June 2008 on 100 patients of clinically non-toxic MNG who underwent thyroid surgery. Biopsy materials were taken from the excised nodules and were sent for histopathological examination to see what proportion of them harboured malignancy. Result: The findings of the study showed that 40% of patients were 30-40 years old with mean age of the patients being 35.5 ± 10.1 (range: 14-75) years. Majority (87%) of the patients was female. Half of the patients with non-toxic MNGs had a history of thyroid swelling for 1-5 years and the rest half for > 5 years with median duration of illness being 5.5 years (range: 1-30 years). Of the 100 patients 4% had stridor and 6% dyspnoea; dysphagia and cervical lymphadenopathy each was 6%. Nearly 60% of the patients had goiter of size 15 sq-cm or below. Sub-total thyroidectomy was the most common operation performed (33%) followed by right hemi-thyroidectomy (24%), near total thyroidectomy (20%), left hemi-thyroidectomy (18%) and total thyroidectomy (5%). Histopathological examination of resected specimens revealed that 15% of the MNGs had malignancy with papillary to follicular carcinoma ratio being 4:1. Histopathological typing showed that 79% was simple MNGs, 4% follicular adenoma, 12% papillary carcinoma, 3% follicular carcinoma and 2% chronic thyroiditis. Neither age nor sex was found to be associated with presence of malignancies in MNGs (p = 0.865 and p = 0.647 respectively). The goiter-size was also not associated with presence of malignancies (p = 0.691). However, the mean duration of thyroid swelling in patients who had malignancy was much higher (8.5 years) than that in patients who did not haveany malignancy (5.7 years) (p = 0.024). Conclusion: The study concluded that a small proportion of long-standing non-toxic MNGs may turn into malignancy. Therefore, routine operative treatment without confirming that the cases are malignant does not seem to be justified. Ibrahim Card Med J 2020; 10 (1&2): 84-88